EDUCATION VALUE IN DIALOGUE AND ADEGAN "GENERAL SOEDIRMAN" MOVIE - Ananda, Rusydi; Ananda, Rizki (Jurnal Sabilarrasyad, 2020)
The value of intelligence is related to critical, logical, creative thinking.  Social values are related to rights and obligations, a sense of responsibility, and an attitude of tolerance.  Religious values related to the spiritual, world and hereafter affairs, lead humans to behave in a moral, virtuous, and be in the way of God.  The value of independence is related to making decisions, self-confidence, being responsible for what is done.  The value of patience is related to not being irritable, not being hopeless, not being heartbroken, and being calm in the face of trials.  The results of General Soedirman's Film study can be used as an alternative teaching material in learning biographical text material at the high school level because there is conformity with the Basic Competencies (KD) "15.1 Reveal interesting things and can be emulated from the characters".  This is seen from the ability of students who can express interesting things and can be emulated from figures from the biography of General Sudirman and able to determine the didactic values contained in the film General Sudirman.  So it can be concluded that the film General Soedirman can be used as an alternative teaching material in biographical text material.